Review of Joint Space Trajectory Planning and Optimization for Industrial Robot - Guo Yong; Lai Guang (Jixie chuandong)
With the development of robotics technology， industrial robots are widely used in automation production， which greatly improves the production efficiency and automation degree. Trajectory planning is the key link to complete the task， and trajectory optimization further improves the quality of mission completion and meets the needs of industrial development. The research progress of trajectory planning and optimization for joint space of industrial robots is reviewed. Firstly， the algorithm of joint space trajectory planning is briefly described. It is pointed out that polynomial interpolation is the main mode， and B-spline curve is an inevitable trend of future development due to its excellent characteristics. Then， the trajectory optimization under different objectives is comprehensively summarized， and the existing problems such as the determination of the optimization objectives and the improvement of the algorithm are pointed out. Finally， the future development direction is prospected. The multi-objective optimization solution and dynamic adjustment of constraints will be the focus of future research.